The Additional Role of the 3-Vessels and Trachea View in Screening for Congenital Heart Disease - Roxana Gireadă; Demetra Socolov; Elena Mihălceanu; Roxana Matasariu; Alexandra Ursache; Mona Akad; Iuliana Bujor; Ioana Scripcariu; Radu Florin Popa; Răzvan Socolov (Medicina, 2022)
Background and Objectives: Although frequent and associated with high mortality and morbidity rate, congenital heart disease (CHD) has a suboptimal prenatal detection rate, with significant variation according to the scanning protocol. The aim of this study was to evaluate the role of the 3-vessels and trachea view (3VT) in detecting CHD, with or without the use of Color Doppler, with an emphasis on major CHD. Materials and Methods: We performed a retrospective study on 1596 unselected pregnant patients presenting at 11–37 weeks of gestation for a routine anomaly scan. We selected all CHD cases, and we analyzed the performance of the 4-chamber (4C) and 3VT view in detecting CHD. Results: A total of 46 fetuses with CHD were identified, yielding a 2.86% overall incidence, and 0.87% for major CHD. Grayscale 4C detected 47.8% of all CHD, going up to 71.7% by adding grayscale 3VT, with no major CHD remaining undetected by combining grayscale 4C and 3VT. Conclusions: Grayscale 4C and 3VT views are effective in detecting major CHD, thus proving their utility even in a low resource setting.